Oxidative stress biomarkers in treatment-responsive and treatment-resistant schizophrenia patients - Buosi, Patrick; Borghi, Fábio Aparecido; Lopes, Angélica Marta; Facincani, Isabela da Silva; Fernandes-Ferreira, Rafael; Oliveira-Brancati, Camila Ive Ferreira; do Carmo, Tayanne Silva; Souza, Dorotéia Rossi Silva; da Silva, Danilo Grünig Humberto [UNESP]; de Almeida, Eduardo Grünig Humberto; de Araújo Filho, Gerardo Maria (My University, 2021)
INTRODUCTION: Schizophrenia is a complex psychiatric disorder that affects approximately twenty million people worldwide. Various factors have been associated with the physiopathology of this disease such as oxidative stress, which is an imbalance between pro-oxidant and antioxidant molecules. OBJECTIVE: This study evaluated the association between biomarkers of oxidative stress and response to pharmacological treatment among patients with schizophrenia in the context of their clinical information, demographic data, and lifestyle. METHODS: A total of 89 subjects were included, 26 of whom were treatment-responsive schizophrenia patients (Group 1), 27 treatment-resistant schizophrenia patients (Group 2), and 36 healthy controls (Group 3). All of the subjects completed a questionnaire to provide clinical and demographic data, and all provided peripheral blood samples. The oxidative stress markers analyzed using spectrophotometry were catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), total glutathione (GSH-t), malondialdehyde (MDA), and Trolox-equivalent antioxidant capacity (TEAC; p < 0.05). RESULTS: When all schizophrenia patients (G1 + G2) were compared to the control group, SOD levels were found to be lower among schizophrenia patients (p < 0.0001), while MDA and CAT levels were higher (p < 0.0001 and p = 0.0191, respectively). GPx, GSH-t, and TEAC levels were similar in all three groups (p > 0.05). CONCLUSION: Lower SOD levels and higher MDA and CAT levels indicate oxidative damage in schizophrenia patients, regardless of their response to pharmacological treatment. Smoking is associated with oxidative stress, in addition, a family history of the disease was also found to be correlated with cases of schizophrenia, which reflects the relevance of genetics in disease development.
Keywords: antioxidants; free radicals; oxidative stress; Psychotic disorders; treatment resistance